The Effect of organizational stress on the Performance of professor at the Faculty of Economics and Commercial Sciences / University of Djelfa / Algeria - كسنة أمحمد; صولي علي (Journal of Economics and Administrative Sciences, 2020)
The present study aims at identifying the effect of organizational pressure with its aspects (management, work team, nature and conditions of work, external environment) on job performance in all its dimensions (commitment and effort made, capabilities and the rapidity of performance, motivation and job satisfaction, work environment) for the university teacher at the Faculty of Economics, Commercial and Management Sciences at the University of Djelfa, Algeria. In this research, the descriptive analytical approach is used. Data was collected through the distribution of a questionnaire to a sample that included 130 permanent teachers before being analyzed using the (SPSS) statistical program. A set of statistical methods has been adopted such as the arithmetic mean, the standard deviation, Pearson correlation coefficient, analysis of variance single ANOVA, and T-test. The research reached a number of results, including: a strong correlation DOES exist between organizational pressures and the job performance of the university teacher at the above-mentioned faculty. an effect relationship could be seen between the aspects of organizational pressure (management, the work team, nature and conditions of work, the external environment) and the job performance of the university teacher at the above-mentioned faculty.